Bio‐derived nanosilica‐anchored Cu(II)‐organoselenium complex as an efficient retrievable catalyst for alcohol oxidation. (9th September 2021) - Gogoi, Rajjyoti; Borah, Geetika
Abstract: A new copper(II) complex supported onto rice‐husk‐derived nanosilica was prepared from 2, 6‐bis((phenylselanyl)methyl)pyridine, salicylaldehyde and copper acetate monohydrate, Cu(OAc)2 ·H2 O. The as‐synthesized complex Cu(II)SeNSe@imine‐nanoSiO2 (Complex I ) was extensively characterized with FT‐IR, powder XRD, SEM‐EDX, solid‐state UV‐Vis, ESR, XPS, TGA and BET surface area analysis. The catalytic activity of the complex was explored for alcohol oxidation reactions using H2 O2 as oxidant and acetonitrile as solvent. For comparison, we have also prepared an analogous homogeneous catalyst (Complex II) and characterized it with FT‐IR, UV‐Vis, LC‐MS and ESR analyses. Its catalytic activity was also screened to the same reaction. The immobilized catalyst showed better efficiency with 75%–95% isolated yield compared with the homogeneous one for alcohol oxidation with at least five times recyclability without profound loss in activity. Abstract : The present research work reports a novel, agro‐waste‐derived nanosilica‐supported six‐coordinated Cu(II) complex with Se–N–Se pincer ligand. This catalyst was screened in the oxidation of alcohols, and we found several advantages such as short reaction time, environmentally benign mild reaction conditions, good to excellent yields, and good stability. The catalyst could be easily separated from the reaction products and reused for at least five successive runs effectively. Highlights: This is the first report of immobilized copper complex with Se–N–Se pincer ligand. Moreover, we have used bio‐derived nanosilica as a solid support. The alcohols are oxidized under environmentally benign mild reaction conditions using hydrogen peroxide as an oxidant. The catalytic performance of the supported complex was compared with an analogous unsupported complex.